Pengaruh Green Accounting, Kinerja Lingkungan, dan Carbon Emission Disclosure terhadap Nilai Perusahaan - Anak Agung Sagung Istri Rima Ulandewi; I Gusti Ayu Intan Saputra Rini; Kadek Goldina Puteri Dewi (Universitas Warmadewa, 2026)
This investigation seeks to scrutinize the influence exerted by green accounting, environmental performance, alongside carbon emission disclosure upon corporate valuation across firms operating within the basic material segment listed on the Indonesia Stock Exchange (IDX) throughout the timeframe spanning 2022 until 2024. A quantitative inquiry framework was utilized through scrutiny of secondary information extracted from corporate annual reports together with sustainability reports. The entire population of basic material enterprises registered on IDX served as the basis, while a sample comprising 40 entities yielding 120 observation points emerged via purposive sampling methodology rooted in pre-established benchmarks. Analytical procedures employed panel data regression utilizing the fixed effect model paradigm executed through EViews 12 software. Empirical outcomes demonstrate that green accounting fails to deliver meaningful influence upon corporate worth, suggesting capital providers have yet to factor environmental-based accounting routines into their assessment frameworks. Environmental performance exhibits an inverse association with firm valuation, mirroring how marketplaces potentially react unfavorably toward ecological enhancements due to supplementary outlays shouldered by corporations. Furthermore, carbon emission disclosure registers no notable consequence upon firm worth. Such conclusions imply that ecological dimensions remain peripheral within investor priorities throughout the basic material industry, where attention persists predominantly upon fiscal indicators alongside global commodity pricing variability. Outputs from this examination are projected to function as reference frameworks aiding stakeholders—comprising firms, regulators, scholars, plus the broader public—in evaluating sustainability initiatives along with their nexus to corporate worth, particularly across industries characterized by pronounced ecological repercussions.